#### Answer

$\frac{9}{16}$

#### Work Step by Step

$(-\frac{3}{4})^{2} = (-\frac{3}{4})(-\frac{3}{4}) = \frac{9}{16}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{9}{16}$

$(-\frac{3}{4})^{2} = (-\frac{3}{4})(-\frac{3}{4}) = \frac{9}{16}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.